2020
DOI: 10.3390/app10062100
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomical-Based Subject-Specific Model of In-Vivo Knee Joint 3D Kinematics From Medical Imaging

Abstract: Biomechanical models of the knee joint allow the development of accurate procedures as well as novel devices to restore the joint natural motion. They are also used within musculoskeletal models to perform clinical gait analysis on patients. Among relevant knee models in the literature, the anatomy-based spatial parallel mechanisms represent the joint motion using rigid links for the ligaments’ isometric fibres and point contacts for the articular surfaces. To customize analyses, therapies and devices, there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 43 publications
(81 reference statements)
0
26
0
Order By: Relevance
“…However, such subject‐specific models are currently much more expensive and time‐consuming to produce relative to generic‐based or ‘averaged’ models and as such have rarely been used to this extent in any species. However, research into the validity of subject‐specific models of the human musculoskeletal system is becoming more widespread, as it is thought that such models may be more accurate for certain tasks than the often used generic or scaled generic models (Lenaerts et al ., 2008; Scheys et al ., 2008; Scheys et al ., 2009; Scheys et al ., 2011; Valente et al ., 2014; Navacchia et al ., 2016; Prinold et al ., 2016; Dejtiar et al ., 2020; Gu and Pandy, 2020; Modenese and Kohout, 2020; Nardini et al ., 2020). For example, models with subject‐specific musculoskeletal geometry have been shown to be more effective for predicting muscle moment arms and joint contact forces, with respective differences of 36% (Scheys et al ., 2008) and 0.61 xBW (Lenaerts et al ., 2008) relative to generic models.…”
Section: Introductionmentioning
confidence: 99%
“…However, such subject‐specific models are currently much more expensive and time‐consuming to produce relative to generic‐based or ‘averaged’ models and as such have rarely been used to this extent in any species. However, research into the validity of subject‐specific models of the human musculoskeletal system is becoming more widespread, as it is thought that such models may be more accurate for certain tasks than the often used generic or scaled generic models (Lenaerts et al ., 2008; Scheys et al ., 2008; Scheys et al ., 2009; Scheys et al ., 2011; Valente et al ., 2014; Navacchia et al ., 2016; Prinold et al ., 2016; Dejtiar et al ., 2020; Gu and Pandy, 2020; Modenese and Kohout, 2020; Nardini et al ., 2020). For example, models with subject‐specific musculoskeletal geometry have been shown to be more effective for predicting muscle moment arms and joint contact forces, with respective differences of 36% (Scheys et al ., 2008) and 0.61 xBW (Lenaerts et al ., 2008) relative to generic models.…”
Section: Introductionmentioning
confidence: 99%
“…The approach was featured by its direct connection with anatomical structures (i.e., the ligaments and articular contacts) and capability to customize to individual subjects and replicate joint passive motion [15]. Recent studies have shown that the knee model based on a spatial parallel mechanism can be personalized by using personal medical images and 3D kinematics data [16,17]. Accurate representation of knee articular features has shown its potential to drive accurate 3D knee joint kinematics during non-weight-bearing knee flexion and extension motions with submillimeter and subdegree errors [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, regardless of the joint constraints imposed, generic (unpersonalized) model-derived kinematics were shown inaccurate (knee kinematic error up to 17° and 8 mm) as these models could not adapt to patient-specific geometry, particularly in pathological conditions (Clément et al, 2017). On the other hand, personalization of model geometry based on medical images was shown promising in improving joint kinematics accuracy (Assi et al, 2016; Clément et al, 2015; Nardini et al, 2020).…”
Section: Introductionmentioning
confidence: 99%